Nature conservation versus climate protection: a basic conflict of goals regarding the acceptance of climate protection measures? - Blöbaum, Anke; Engel, Lukas; Beer, Katrin; Böcher, Michael; Matthies, Ellen (Frontiers in Psychology, 2023)
Transformation processes are embedded in a broader discourse on sustainability, climate protection, and biodiversity protection. In this context, possible interindividual conflicts between an interest in nature conservation and efforts to counteract climate change also seem to be relevant. This study focuses on the acceptability of different climate protection measures with possible impacts on landscapes, habitats, and human recreation. Based on a survey of a representative sample (N = 1,427 participants), the impact of conservation-related beliefs on the acceptance of four different climate protection measures was analyzed with respect to possible conflicts with values and norms relevant to climate protection. The study focuses in particular on potential value-based conflicts, as this type of conflict is classified as non-negotiable in negotiation processes and thus represents a particular social challenge. Also, to consider the possible relevance of political orientation and humanity orientation, eight structural equation models were tested. Results showed similar structures for the acceptance of the four climate protection measures. There did not seem to be value-based conflicts between nature conservation and climate protection, as the results showed substantial similarities between nature conservation beliefs grounded in biospheric value orientation (protecting biodiversity) and values and norms relevant for climate protection. Political orientation seemed to be relevant as well, as left-oriented people were more likely to accept the four climate protection measures that were tested. However, the relationship between political orientation and acceptance of the measures was – without exception – mediated by the personal norm.